The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7307/ptt.v29i2.2071
|View full text |Cite
|
Sign up to set email alerts
|

The Driver Behaviour and Impact of Speed on Road Safety on the Motorways in Croatia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Experienced drivers mostly disobey the speed limit signs in expressway accident segments, but most novice drivers basically obey the speed limit signs. This is similar to the conclusions obtained by Zovak et al [5]. They believed that drivers especially obey the speed limits in tunnels, and only a certain number of drivers obey the speed limits on expressways.…”
Section: Analysis Of Decelerating Behaviorsupporting
confidence: 91%
See 1 more Smart Citation
“…Experienced drivers mostly disobey the speed limit signs in expressway accident segments, but most novice drivers basically obey the speed limit signs. This is similar to the conclusions obtained by Zovak et al [5]. They believed that drivers especially obey the speed limits in tunnels, and only a certain number of drivers obey the speed limits on expressways.…”
Section: Analysis Of Decelerating Behaviorsupporting
confidence: 91%
“…Many studies have shown that excessive speed is one of the major factors to cause traffic accidents. A speed limit is a widely adopted measurement to improve traffic safety [5]. Speed limit signs showing the maximum or minimum speed value guide drivers to adjust vehicles' speed.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [16] establish that excess speed is one of the most significant causes of traffic accidents. Accordingly, the authors in [10] quote that aggressive driving style can be used as a "catch-all" for all intensity of maintenance of a vehicle is determined by the number of kilometres travelled by the vehicle in an observed period of time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In segment N i! (1,2,...,Nm) , during the discrete-time instant t=kΔt (k=0,1,...,k p ), where k p is the time frame, the average number of vehicles on each kilometre of road space is denoted as traffic density ρ m,i (k). The number and the average speed of vehicles flowing into segment N i are denoted as q m,i (k) and v m,i (k), respectively.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Some studies indicated that a reasonable speed limit on freeway can improve transport service quality [1,2]. The Variable Speed Limits (VSL) control, as a popular mainline traffic control approach, is applied widely in the field of transportation.…”
Section: Introductionmentioning
confidence: 99%